The Applicable Law on Personal Status of Refugees: A Comparative Analysis of Iranian Law and the 1951 Refugee Convention - Hossein KAVIAR; Mehdi Amini; Maryam Ghorbanifar (پژوهش های حقوق تطبیقی)
Private international lawyers can no longer believe that asylum rules belong only to public international law, or that asylum is not the core of private international law. On the contrary, private international law should be the first branch of law to address asylum and its impact on the personal status of individuals. Cross-border flight by people who fear for their lives or freedom raises important issues in the field of their private international law. In addition to the logistical issues related to asylum seekers, destination countries also face issues related to their private international law in the field of personal status. This article examines one of the long-term legal concerns, namely the portability of the personal status of refugees across borders. Article 12 of the Convention on the Status of Refugees makes their personal status subject to the law of their country of residence. Considering Iran's accession to this Convention, the rule of Article 7 of the Civil Code will not apply to them, and the law governing the personal status of refugees must be determined differently from that of other foreign nationals. The findings of this research show that according to Iranian private international law, the governing law for the personal status of refugees residing in Iran should be determined with due regard to their religion or faith. If, according to Article 12 of the Convention, we consider Iranian law to be the governing law of residence, it can be said that the religious rules of minorities recognized in the Constitution, as part of Iranian law, can also be applied to refugees. It is obvious that where the refugee is not a member of Iran's recognized minorities, his personal status will be subject to the law of his residence.